Turbulent heat transport in TOKAM3X edge plasma simulations. Issue 6 (6th June 2018) - Baudoin, Camille; Tamain, Patrick; Bufferand, Hugo; Ciraolo, Guido; Fedorczak, Nicolas; Galassi, Davide; Ghendrih, Philippe; Nace, Nicolas
Abstract : The recent version of the 3D fluid code TOKAM3X, including self‐consistent variation of both electron and ion temperature, is used to investigate the properties of energy turbulent structures and heat transport. We also make a comparison with the results of the isothermal equivalent simulation. The studied regime is an L‐mode‐like regime where both particle and heat transport are dominated by turbulence with Γturb /Γtot > 80% and the turbulence features are found to be similar in isothermal and anisothermal models. However, the presence of a significant shear at the separatrix in the anisothermal version modifies the penetration length of turbulent structures into the scrape‐off layer, and seems to trigger the appearance of a sharper gradient at the separatrix, reminiscent of the narrow feature observed in the experiment.